PENTINGNYA MINAT DAN BAKAT DALAM MEMILIH PROGRAM STUDI YANG PROSPEKTIF DI INDUSTRI MELALUI BIMBINGAN DAN KONSELING KARIR DI SEKOLAH MENENGAH KEJURUAN [THE IMPORTANCE OF INTEREST AND TALENT IN CHOOSING A PROSPECTIVE STUDY PROGRAM IN INDUSTRY THROUGH CAREER GUIDANCE AND COUNSELING IN VOCATIONAL SECONDARY SCHOOL] - Yonanda, Nadia Rista; Iswari, Mega; Daharnis, D (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2022)
This research is motivated by the difficulty of choosing the right learning program because vocational students do not have clear goals and career plans. Therefore, this study aims to determine the importance of interest and talent in choosing the right study program towards a prospective career in industry through career guidance in vocational schools. This study uses a literature study method with the finding that career guidance is one of three areas of guidance and counseling services, namely tutoring, social guidance, and personal guidance. The vocational high school guidance program aims to help students to plan their professional future by making career choices according to their talents and interests. In this case, talents and interests are very important for that guidance and counseling teachers help students to recognize their potential such as adjusting their interests and talents to the chosen study program so that the study program can be said to be right. Finally, career guidance not only provides answers to problems that arise, but also helps students acquire the knowledge, attitudes, and skills that students need for their profession or future career.